Study on the Coarsening Behavior of Interphase Precipitates and Random Precipitates in Steel Under the High-Temperature Environment of Fire - Jinghua Cong; Yongzhe Yang; Haibin Zhu; Xueliang Shang; Hongyu Wu; Zhendong Song; Xuemin Wang; Xiangyu Xu (Metals)
In the domain of fire-resistant steels, the characteristics of precipitates significantly influence material properties. This study developed a novel heat treatment protocol to concurrently achieve both interphase precipitation and random precipitation. Samples were subjected to isothermal treatments at various temperatures and durations, while techniques such as scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were employed to thoroughly analyze the coarsening behavior of the two types of precipitate and reveal their thermal stability differences. The results show that the growth and coarsening rates of interphase precipitates are substantially lower than random precipitates. Coarsening kinetics analysis reveals that the radius of random precipitates follows a 1/3 power law with time at 600 °C and 650 °C, whereas the radius of interphase precipitates adheres to a 1/6 power law at 600 °C and a 1/5 power law at 650 °C. Furthermore, interphase precipitation demonstrates excellent size uniformity, which hinders the formation of a concentration gradient, thereby reducing the coarsening rate and enhancing thermal stability. After prolonged tempering treatment, interphase precipitation maintains a higher strengthening contribution than random precipitation. This study provides novel insights and theoretical foundations for the design and development of fire-resistant steels.